Challenges and opportunities faced by an insider researcher in Malaysian ethnicity studies : a literature review - Khauthar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ethnicity in most social contexts is largely treated as a simple and reified concept especially by insider researchers in post-colonial countries. In certain cases, some of these insider researchers have a perception that being part of an ethnic group would primordially equip them with prior knowledge about their group, hence neglecting the complexity of the ethnicity itself. The outcomes would be problematic for the development of ethnicity studies: theoretically and methodologically. The main objective of this article is to discuss methodological (epistemological and ontological) challenges faced by insider researchers in Malaysian ethnicity studies. Using the Extended Case Method (ECM), I reflect on how I engaged methodologically as an insider researcher in understanding ethnicity. The discourse is intended to assist insider researchers in justifying their methodological perspective in ethnicity studies without neglecting their identity and position.